UPAYA PENINGKATAN KETERAMPILAN GURU DALAM PENERAPAN PEMBELAJARAN AKTIF, KREATIF, EFEKTIF, DAN MENYENANGKAN (PAKEM) MELALUI KEGIATAN PELATIHAN DAN BIMBINGAN (LATBIM) DI SDN 14 BATANG GASAN - Yuslina Yuslina (STKIP Pesisir Selatan, 2018)
ABSTRACT Based on the observations that researchers have made to the Teachers at Batang Gasan Elementary School 14, it was found that the teacher's skills in implementing Active, Creative, Effective and Fun (PAKEM) learning were still low. The purpose of this study was to improve teacher skills in the application of PAKEM through training and guidance activities (LATBIM) in Batang Gasan Elementary School 14. This research is a school action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 6 Batang Gasan Elementary School Teachers. Research data was collected using observation sheets. Data is analyzed using percentages. The results showed that Training and Guidance Activities could improve Teacher Skills in the application of active, Creative, Effective and Fun (PAKEM) learning in Batang Gasan Elementary School 14. This is evidenced by an increase in the ability of teachers in the application of Active, Creative, Effective and Fun (PAKEM) learning from cycle I to cycle II. The average ability of teacher skills in the application of PAKEM learning in the first cycle was 49.66 in the Less category and in the second cycle was 82.33 in the good category.Keywords: Improving teacher skills, application of PAKEM learning, training and guidance (LATBIM).